Management education in Canada
1 online resource.
Keywords: "Management Education in Canada: Historical Reflections offers a fresh and critical look at the evolution of management education in Canada. Nearly 25 years after the seminal work Capitalizing Knowledge by Barbara Austin, this edited collection revisits and expands upon the debates that shaped the field, while introducing new perspectives and overlooked histories. Featuring ten scholarly essays from leading academics, this volume explores a range of critical and historiographic approaches to management education, highlighting the ways in which history is written, privileged, and, at times, neglected. Through a variety of themes, including the gendered experiences of female PhD graduates, Africentric and Indigenous leadership approaches, and the role of globalization in shaping management curricula, the book prompts readers to reflect on the past, present, and future of management education in Canada. Chapters cover topics such as the influence of the Administrative Sciences Association of Canada, the underrepresentation of French-language business education, and the critical interrogation of management textbooks. Together, these chapters offer a rich and comprehensive analysis of the cultural, institutional, and intellectual forces shaping the discipline. This volume will engage scholars, educators, and students in business schools, faculties of management, and those interested in the broader history of higher education, as well as anyone seeking to understand the historical development of management education in Canada. It is an essential contribution to the ongoing conversation about what management education has been and what it could become"-- Provided by publisher.